The Turkish Adaptation of the McClosky and Mueller Job Satisfaction Scale: A Reliability and Validity Study - Gizem Bayrakçı; Emine Türkmen (Dokuz Eylul University, 2020)
Background: Job satisfaction is an important factor in the retention of nurses. There are a few valid and reliable scales to evaluate job satisfaction for nurses in Turkey. Objectives: This methodological study was performed to determine whether the Turkish version of the "McCloskey and Mueller Job Satisfaction Scale/MMSS" is a valid and reliable tool for nurses in Turkey. Methods: This study was conducted with 324 nurses in three hospitals in Istanbul between June and August 2017. The study data collected using the "Descriptive Characteristics Form", and "McCloskey and Mueller Job Satisfaction Scale" consisting of 31 items. Results: The scale content validity index was 0.93. The Cronbach's alpha reliability coefficient was 0.81 for the overall scale and ranged from 0.45 to 0.70 for the sub-dimensions. The stability of the scale over time was tested with 32 nurses twice at a 15-day interval. There was no significant difference between the two measurements. The item-total score reliability coefficient of the scale ranged between 0.28 and 0.49. In the confirmatory factor analysis, the path coefficients of the items with their dimension (eight sub-dimensions) ranged between 0.36 and 0.64. The goodness of fit of the model determined in the confirmatory factor analysis was at an acceptable level (Chi square / Degree of freedom: 1.4, p  .05). Conclusion: The results of this study indicated that MMSS meets the content and construct validity criteria. Although reliability tests of the MMSS, which are item analysis and stability, are acceptable range there is a need for further research to test the reliability of Cronbach alpha on the sub-dimensions of the MMSS.